Proteomic based approach for characterizing 4-hydroxy-2-nonenal induced oxidation of buffalo (Bubalus bubalis) and goat (Capra hircus) meat myoglobins. Issue 1 (December 2016) - Maheswarappa, Naveena; Rani, K.; Kumar, Y.; Kulkarni, Vinayak; Rapole, Srikanth
Abstract Background Myoglobin (Mb) is a sarcoplasmic heme protein primarily responsible for meat color and its chemistry is species specific. 4-hydroxy-2-nonenal (HNE) is a cytotoxic lipid derived aldehyde detected in meat and was reported to covalently adduct with nucleophilic histidine residues of Mb and predispose it to greater oxidation. However, no literature is available on characterization of lipid oxidation induced oxidation of Indian water buffalo (Bubalus bubalis ) and goat (Capra hircus ) myoglobins. Methods Present study characterize the Mb extracted from water buffalo and goat cardiac muscles using two-dimensional gel electrophoresis (2DE), OFFGEL electrophoresis and mass spectrometry (MS). Purified buffalo and goat bright red oxymyoglobin were reacted with HNE in-vitro at physiological pH (7.4) and temperature (37 °C) conditions and the formation of oxidised brown metmyoglobin was measured. The Mb-HNE adducts were detected using MALDI-TOF MS, whereas specific sites of adduction was determined using ESI-QTOF MS/MS. Results Purified buffalo and goat Mb samples revealed a molecular mass of 17, 043.6 and 16, 899.9 Daltons, respectively. The 2DE analysis exhibited 65 (sarcoplasmic protein extract) and 6 (pure Mb) differentially expressed (P < 0.05) protein spots between buffalo and goat samples. OFFGEL electrophoresis revealed an isoelectric point of 6.77 and 7.35 respectively, for buffalo and goat Mb's. In-vitro incubation of HNE with bright red buffalo and goat oxymyoglobin's at pH 7.4 and 37 °C resulted in pronounced (P < 0.05) oxidation and formation of brown metmyoglobin. MALDI-TOF MS analysis of Mb-HNE reaction mix revealed covalent binding (via Michael addition) of 3 and 5 molecules of HNE with buffalo and goat Oxy-Mb's, respectively. ESI-QTOF MS/MS identified seven and nine histidine (HIS) residues of Mb that were readily adducted by HNE in buffalo and goat, respectively. Conclusion The study demonstrated better redox stability of buffalo Mb than goat Mb. Our findings confirm the hypothesis that relative effect of HNE was greater for Mb's with 12 ± 1 HIS residues than Mb's with 9 HIS residues and helps meat processors in developing species-specific processing strategies to reduce the color variability.